2021
DOI: 10.21742/ijsbt.2021.9.1.06
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Service Quality of Internet Insurance on Intention to Purchase Online

Abstract: With the development of information technology making, it easier to share information and increasing the number of insurance consumers who are accustomed to using digital devices, interest in Internet insurance, in which insurance companies and insurance consumers decide their choice of insurance products on their own, is gradually increasing. Internet insurance is expected to grow dramatically due to convenience of use, low insurance premiums, composition of consumer-oriented products, various information dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In previous research, it has been widely stated that the quality of information significantly impacts consumers' intentions to use Insurtech. [19] found that factors such as transaction speed, competitiveness of insurance premiums, and information quality have a positive and significant influence on consumer usage intentions. Another researcher, [20], highlighted the importance of implementing appropriate information technology in shaping consumer perceptions of information quality.…”
Section: Methodsmentioning
confidence: 99%
“…In previous research, it has been widely stated that the quality of information significantly impacts consumers' intentions to use Insurtech. [19] found that factors such as transaction speed, competitiveness of insurance premiums, and information quality have a positive and significant influence on consumer usage intentions. Another researcher, [20], highlighted the importance of implementing appropriate information technology in shaping consumer perceptions of information quality.…”
Section: Methodsmentioning
confidence: 99%